2003
DOI: 10.1038/sj.npp.1300175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naltrexone Alone and In Combination With Acamprosate on the Alcohol Deprivation Effect in Rats

Abstract: Previous research in our laboratory has shown that responding for ethanol increases after a period of imposed deprivation during which no ethanol is available (the alcohol deprivation effect). This selective increase in responding for ethanol was blocked by chronic administration of acamprosate. In the present study the effects of naltrexone and the combination of naltrexone+acamprosate on oral ethanol self-administration were examined following an imposed period of abstinence. Male Wistar rats were trained to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 58 publications
8
78
0
Order By: Relevance
“…In contrast, when the animals passed periods of abstinence only from alcohol, they only showed a temporary increase in their EtOH consumption. This last finding is in agreement with most studies (Heyser et al, 1998(Heyser et al, , 2003RoddHenricks et al, 2000;Samson et al, 2001;Serra et al, 2002;Cowen et al, 2003;Vengeliene et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, when the animals passed periods of abstinence only from alcohol, they only showed a temporary increase in their EtOH consumption. This last finding is in agreement with most studies (Heyser et al, 1998(Heyser et al, , 2003RoddHenricks et al, 2000;Samson et al, 2001;Serra et al, 2002;Cowen et al, 2003;Vengeliene et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…The alcohol deprivation effect is a useful model for monitoring alcohol relapse. In this study, we used male Wistar rats, which have been shown to develop the alcohol deprivation effect Spanagel et al, 1996;Heyser et al, 1998Heyser et al, , 2003. However, rats exposed to WIN 55,212-2 showed a persistent increase in responding for alcohol (over 2 weeks), abolishing the characteristic temporality of increase of alcohol intake of the alcohol deprivation effect (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responding for cues predictive of water availability was not influenced by acamprosate treatment. The selectivity of the effect of acamprosate over the range of doses used here is consistent with results obtained in previous studies in which this drug was tested on ethanol self-administration or on the alcohol deprivation effect under operant conditions (Hölter et al, 1997;Heyser et al, 1998Heyser et al, , 2003.…”
Section: Discussionsupporting
confidence: 79%
“…Opiate antagonists (Heinälä et al 2001;Litten and Allen 1998;O'Malley et al 1992;Monti et al 2001;Rubio et al 2001;Volpicelli et al 1992), acamprosate (Ansoms et al 2000;Besson et al 1998;Chick et al 2000;Lesch et al 2001;Rubio et al 2001;Sass et al 1996;Tempesta et al 2000;Litten and Allen 1998; see overview by Mason 2001) or a combination of these drugs (Kranzler and Van Kirk 2001) are currently prescribed to reduce alcohol consumption in alcoholics. In preclinical studies, opiate antagonists are capable of minimizing acute drinking of alcohol (Altshuler et al 1980;Badia-Elder et al 1999;Froehlich et al 1990;Heyser et al 2003;Hölter and Spanagel 1999;Hyytia and Sinclair 1993;Overstreet et al 1999;Samson and Doyle 1985), as well as reducing alcohol seeking by an alcohol conditioned stimulus (Liu and Weiss 2002a;Koob et al 2003). However, naltrexone's maintenance of abstinence in alcoholdependent patients was not remarkable in one study (Guardia et al 2002) and was absent in another (Krystal et al 2001).…”
Section: Future Directionsmentioning
confidence: 99%